Effectiveness and safety of acupuncture as an adjunctive therapy for chronic obstructive pulmonary disease: a randomised controlled trial - Guixing Xu; Qin Luo; Mingsheng Sun; Liuyang Huang; Jiali Liu; Chunyan Yang; Qingsong Huang; Chan Xiong; Zuoqin Yang; Sha Yang; Fang Zeng; Fanrong Liang (BMC, 2024)
Abstract Background The effectiveness and safety of acupuncture therapy to delay lung function decline in chronic obstructive pulmonary disease (COPD) remain unclear. This study aimed to determine whether acupuncture, as an adjunctive therapy to COPD-guided medication, could prevent lung function decline. Methods This randomised, two-centre study was conducted between February 2022 and July 2023. Men and women aged 40-80 years with COPD were recruited. Participants received active or sham acupuncture three times a week (36 sessions total). The primary outcome was the change in the percentage of forced expiratory volume for 1 s to the predicted value (FEV1%) between the baseline and after the intervention. Results Overall, 238 participants were screened, and 74 (58 men [78.4%]; mean [standard deviation] age, 69.6 [7.2] years) were randomised into the acupuncture and sham acupuncture groups (37 per group). After the intervention, the change in FEV1% was 1.35 (95% confidence interval [CI]: -0.47 to 3.17) and -2.44 (95% CI: -4.56 to -0.33) in the acupuncture and sham acupuncture groups, respectively. The difference was -3.97 (95% CI: -6.2 to -1.74), and the adjusted difference was -3.46 (95% CI: -5.69 to -1.24, P = 0.003) between the groups. A significantly less decline was found in forced expiratory volume for 1 s in the acupuncture group. All treatment-related adverse events (acupuncture = 11, sham = 2) were mild. Conclusions Compared with sham acupuncture, acupuncture plus medication may delay lung function decline. However, further studies with a larger sample size and longer-term follow-up are needed to clarify the effects.